'Digital by Default' and the 'hard to reach': Exploring solutions to digital exclusion in remote rural areas. (November 2016) - Williams, Fiona; Philip, Lorna; Farrington, John; Fairhurst, Gorry
In the UK, the geography of Information and Communication Technology (ICT) infrastructure required for Internet connectivity is such that high speed broadband and mobile phone networks are generally less available in rural areas compared with urban areas or, in other words, as remoteness and population sparsity increase so too does the likelihood of an area having no or very poor broadband connectivity. Against a policy backdrop of UK Government efforts to bring forward network infrastructure upgrades and to improve the accessibility of broadband services in locations where there is a weak commercial investment case, this paper considers the options for the 'final few' in the prevailing 'Digital by Default' public services context. The paper outlines the Rural Public Access WiFi Services project, a study focused upon enabling Internet connectivity for commercially 'hard to reach' rural areas in the UK. The Rural Public Access WiFi Services concept and the experiment are introduced before findings from a pilot deployment of a broadband service to households in a remote rural area, who may be classified as 'digitally excluded', are presented. The paper then reflects on our field experiment and the potential of the Rural Public Access WiFi Services service model as a solution to overcoming some of the digital participation barriers manifest in the urban–rural divide. Early indications show that the Rural Public Access WiFi Services model has the potential to encourage participation in the Digital Economy and could aid the UK Government's Digital by Default agenda, although adoption of the model is not without its challenges.